Michael Skidmore v Led Zeppelin: Copyright infringement in music under US law. (24th April 2020) - Bosher, Hayleigh
Abstract: Michael Skidmore v Led Zeppelin No 16-56057, DC No 2:15-cv-03462-RGK-AGR, 9 March 2020 The US Ninth Circuit Court of Appeal upheld that Led Zeppelin's song Stairway to Heaven did not infringe the copyright of the instrumental song 'Taurus' and overruled circuit precedent to reject the inverse ratio rule.